Palladium-Gold Nanoalloy Surface Modified LiMn2O4 Cathode for Enhanced Li-Ion Battery. (20th April 2015) - Ross, Natasha; Nzaba, Myra; Ntuthuko, Wonderboy; Ikpo, Chinwe; Baker, Priscilla; Iwuoha, Emmanuel
Abstract : Au with Pd nanoparticles were synthesized and coated onto the spinel LiMn2 O4 via a coprecipitation calcination method with the objective to improve the microstructure, conductivity, and electrochemical activities of pristine LiMn2 O4 . The novelLi PdAu x M n 2 - x O 4 composite cathode had high phase purity, well crystallized particles, and more regular morphological structures with narrow size distributions. At enlarged cycling potential ranges theLi PdAu x M n 2 - x O 4 sample delivered 90 mAh g −1 discharge capacity compared to LiMn2 O4 (45 mAh g −1 ). It was concluded that even a small amount of the Pd and Au enhanced both the lithium diffusivity and electrochemical conductivity of the host sample due to the beneficial properties of their synergy.